High Temperature Induced Anthocyanin Inhibition and Active Degradation in Malus profusion - Rehman, Rana Naveed Ur; You, Yaohua; Zhang, Lei; Goudia, Bachir Daoura; Khan, Abdul Rehman; Li, Pengmin; Ma, Fangwang (Frontiers in Plant Science, 2017)
The red fleshed fruits of Malus profusion represent gradual color loss during high temperature in summer, potentially due to active degradation of anthocyanin. The objective of this study was to examine both physiological and molecular evidence of anthocyanin degradation. Malus crabapple fruits were exposed to either room temperature (RT = 18±2°C: 25±2ºC) or high temperature (HT = 33±2°C: 25±2ºC) regimens (12 h: 12 h) under hypoxic (2%) or normoxic (21%) oxygen levels. The results showed that the concentration of cyanidin 3-galactoside (cy-3-gal) was dramatically reduced following HT treatments due to a significant down-regulation of anthocyanin biosynthetic genes (MpCHS, MpDFR, MpLDOX, MpUFGT and MpMYB10). Among other repressor MYBs, MpMYB15 expression was high following HT treatment of the fruit. HT led to the generation of a substantial concentration of H2O2 due to enhanced activities of superoxide dismutase (SOD), methane dicarboxylic aldehyde (MDA) content and cell sap pH value. Similarly, transcript levels of MpVHA-B1 and MpVHA-B2 were reduced which are involved in the vacuolar transportation of anthocyanin. The enzymatic degradation of anthocyanin was eventually enhanced coupled with the oxidative activities of peroxidase (POD) and H2O2. Conversely, the RT treatments potentially enhanced anthocyanin content by stabilizing physiological attributes (such as MDA, H2O2, and pH, among others) and sustaining sufficient biosynthetic gene expression levels. Quantitative real-time PCR analysis indicated that the transcription of MpPOD1, MpPOD8 and MpPOD9 genes in fruit tissues was up-regulated due to HT treatment and that hypoxic conditions seems more compatible with the responsible POD isoenzymes involved in active anthocyanin degradation. The results of the current study could be useful for understanding as well as elucidating the physiological phenomenon and molecular signaling cascade underlying active anthocyanin degradation in Malus crops.